Small and Medium-Sized Enterprises as a Driver of Innovative Development of the Russian Fuel and Energy Complex - Kapitonov, Ivan A.; Voloshin, Vladimir I.; Zhukovskaya, Irina V.; Shulus, Aleksei A. (International Journal of Energy Economics and Policy, 2017)
The urgency of the studied problem is caused by the fact that international sanctions led to a number of bans in the oil and gas industry, and there is the necessity to create the role of small and medium-sized innovative enterprises. In this regard, this article is aimed at identifying the positive and negative aspects of these enterprises, as well as their significance in the development of the oil and gas service segment. Keywords: fuel and energy complex, innovative enterprises, international sanctions, import substitution, territorial clusters JEL Classifications: O13, P18, M21